Emerging Mechanisms Underpinning Neurophysiological Impairments in C9ORF72 Repeat Expansion-Mediated Amyotrophic Lateral Sclerosis/Frontotemporal Dementia - Pasniceanu, Iris-Stefania; Atwal, Manpreet Singh; Souza, Cleide Dos Santos; Ferraiuolo, Laura; Livesey, Matthew R. (Frontiers in Cellular Neuroscience, 2021)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are characterised by degeneration of upper and lower motor neurons and neurons of the prefrontal cortex. The prominence of the C9ORF72 repeat expansion mutation as the leading genetic cause of ALS and the second leading cause of FTD has led to a progressive understanding of the multiple cellular pathways leading to neuronal degeneration. Disturbances in neuronal function represent a major subset of these mechanisms and because such functional perturbations precede degeneration, it is likely that impaired neuronal function in ALS/FTD plays an active role in pathogenesis. This is supported by the fact that ALS/FTD patients consistently present with neurophysiological impairments prior to any apparent degeneration. In this review we summarise how the discovery of the C9ORF72 repeat expansion mutation has contributed to the current understanding of neuronal dysfunction in ALS/FTD. We will discuss this in the context of the impact of the repeat expansion on neuronal function including intrinsic excitability, synaptic, network and ion channel properties, highlighting evidence of conserved and divergent pathophysiological impacts between cortical and motor neurons and the influence of non-neuronal cells. We further highlight emerging evidence of the association of these dysfunctional properties with molecular mechanisms of the hexanucleotide repeat expansion mutation that appear to include roles for both haploinsufficiency of the C9ORF72 protein and aberrantly generated dipeptide repeat protein species. We finally suggest that relating key pathological observations in C9ORF72 repeat expansion ALS/FTD patients to the mechanistic impact of the C9ORF72 repeat expansion on neuronal function will lead to an improved understanding of how neurophysiological dysfunction impacts upon pathogenesis.